M12 52 month follow up of patients with IPF receiving nintedanib via the compassionate use programme. (12th November 2019) - Ward, K; Ind, P; Woods, D; Springett, J; Dos Santos, C; Hunt, C; Coker, R
Abstract : Introduction: In 2015 nintedanib became available on a compassionate use programme (CUP) to patients with idiopathic pulmonary fibrosis (IPF), after the 2014 publication of the INPULSIS trial 1 and before receiving National Institute for Health and Care Excellence (NICE) approval in England and Wales in January 2016. 2 NICE subsequently approved nintedanib with the same limited forced vital capacity (FVC) criteria as for pirfenidone: 50–80% predicted (pred). The nintedanib CUP allowed patients with FVC >80% pred to receive anti-fibrotic treatment, and many have continued to take nintedanib for over 4 years. We have reviewed our single centre cohort of real-life IPF patients and examined outcomes. Methods: We retrospectively identified patients who consented to receive nintedanib under the CUP from 1st February 2015 and who had more than one FVC recorded. We obtained demographic, lung function and mortality data from the electronic medical record. We collected data to 1st June 2019. We compared CUP patients to the patients in the INPULSIS trial (1) performing statistics using GraphPad Prism. Results: Our patients were older, had higher baseline FVC measurements and were followed for longer, but had greater reductions in lung function over time (table 1). Six of 23 (26%) patients died over a 52 month period in our observational study compared to 35 out of 638 (5.5%) over 12 months in INPULSIS 1 and 2 combined. 1 Discussion: We studied real-life IPF patients who tended to be older than in the pivotal regulatory clinical trial.(1) Direct statistical comparisons were not possible without the raw data but baseline absolute FVC values were similar. However, our patients represent earlier or milder disease: 74% would not have qualified for nintedanib on NICE criteria. These data provide insights into treatment of older and high FVC patients with nintedanib. References: Richeldi L, et al . NEJM. 2014;370(22):2071–82. NICE Technology Appraisal Guidance (TA379). 2016.